PENGARUH KEPEMIMPINAN DAN KARAKTERISTIK PEGAWAI TERHADAP PRESTASI KERJA PEGAWAI DI DINAS PERHUBUNGAN KOMUNIKASI DAN INFORMATIKA KABUPATEN KERINCI - Siswadhi, Ferry; Ahmad, Mauledy (Jurnal Benefita, 2017)
This research -Research influence of leadership and characteristics of employees on work performance of employees, the study was conducted in the transportation department, communication and informatics Kerinci district. In this study used data collection method is the method of library research and field research. In this study, the samples are civil servants in the transportation department, communication and informatics Kerinci district. Used Test Validity and Test Reliability in this study and also using multiple linear regression analysis and coefficient of determination. The results of the analysis showed that simultaneous leadership and employee characteristics have a significant effect on the performance of employees. Variables of leadership and the characteristics of each employee has a significant influence on employee job performance variable. Judging from the partial determination coefficient (r2) is known the influence of leadership on the performance of employees is equal to 0.869 or 86.90%. The amount of influence the characteristics of employees on work performance of employees is equal to 0.821 or 82.11% .variable leadership is the most dominant influence variable to variable work performance of employees at the Department of Communication and Information Kerinci.